2013
DOI: 10.1097/mao.0b013e3182804b31
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Nerve Deficiency and Associated Clinical Features in Patients With Bilateral and Unilateral Hearing Loss

Abstract: Our results suggest differences in the causes and mechanisms of CND in children with bilateral versus unilateral hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 10 publications
9
37
0
1
Order By: Relevance
“…Similar to the fin-dings of the current study, the cochlear nerve surface area of the patients with idiopathic hearing loss and loss associated with connexin26 gene mutation was determined to be smaller than that of the ears with normal hearing. Nakano et al evaluated the computed tomography (CT) findings of children with congenital hearing loss, and again similar to the findings of the current study, the cochlear nerve canal was found to be smaller in children with hearing loss 9. …”
supporting
confidence: 86%
“…Similar to the fin-dings of the current study, the cochlear nerve surface area of the patients with idiopathic hearing loss and loss associated with connexin26 gene mutation was determined to be smaller than that of the ears with normal hearing. Nakano et al evaluated the computed tomography (CT) findings of children with congenital hearing loss, and again similar to the findings of the current study, the cochlear nerve canal was found to be smaller in children with hearing loss 9. …”
supporting
confidence: 86%
“…As UNHS now allows for better identification of children with UHL, the most common time of onset is now understood to be congenital, accounting for 45% of infants and children with sensorineural UHL (Ghogomu et al, 2014). Of congenital causes, it appears that cochlear nerve deficiency may be the most common, accounting for up to 50% of children with congenital severe-to-profound UHL (Nakano, Arimoto, & Matsunaga, 2013). For the purposes of prevention, acquired causes of HL including infections such as congenital cytomegalovirus (CMV) (Kumar et al, 1984) and meningitis (Fortnum & Davis, 1993), as well as temporal bone trauma (Morgan, Coker, & Jenkins, 1994) should be recognized (See Table 1).…”
Section: Causes Of Unilateral Hearing Lossmentioning
confidence: 99%
“…Unilateral hearing loss is more common than bilateral [20], and it was previously reported that more than one out of ten children initially diagnosed with unilateral hearing loss will progress to bilateral hearing loss [21][22][23]. Cochlear nerve deficiency is the most common type of malformation observed in the setting of congenital unilateral hearing loss [24][25][26]. Although there are reports of familial unilateral hearing loss [27][28][29][30], genetic mutations associated specifically with unilateral hearing loss have yet not been identified with certainty [31].…”
Section: Discussionmentioning
confidence: 99%